2014
DOI: 10.1186/s12868-014-0125-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Edaravone and Scutellarin in activated microglia in experimentally induced ischemia injury in rats and in BV-2 microglia

Abstract: BackgroundIn response to cerebral ischemia, activated microglia release excessive inflammatory mediators which contribute to neuronal damage. Therefore, inhibition of microglial over-activation could be a therapeutic strategy to alleviate various microglia-mediated neuroinflammation. This study was aimed to elucidate the anti-inflammatory effects of Scutellarin and Edaravone given either singly, or in combination in activated microglia in rats subjected to middle cerebral artery occlusion (MCAO), and in lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 47 publications
1
74
0
Order By: Relevance
“…With respect to multiple sclerosis, encouraging studies in the model of experimental allergic encephalomyelitis already exist42. It is of interest that edaravone rescues oligodendrocyte differentiation after prolonged ischemic damage in mice43, reduces white matter injury in a mouse model of hypoxic-ischemia44, and has anti-inflammatory effects in activated microglia45. The identification of two active analogs of edaravone and the purity analysis validated its biological and structural activity, allowing us to conclude that the remyelinating activity of edaravone is not a false positive.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to multiple sclerosis, encouraging studies in the model of experimental allergic encephalomyelitis already exist42. It is of interest that edaravone rescues oligodendrocyte differentiation after prolonged ischemic damage in mice43, reduces white matter injury in a mouse model of hypoxic-ischemia44, and has anti-inflammatory effects in activated microglia45. The identification of two active analogs of edaravone and the purity analysis validated its biological and structural activity, allowing us to conclude that the remyelinating activity of edaravone is not a false positive.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Yuan et al [46] demonstrated anti-inflammatory effects of edaravone in stroke animals, focusing on inflammatory cytokines from activated microglia in the brain. Our current study may expand the previous finding from novel aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EDA, a ROS scavenger, inhibits the release of proinflammatory cytokines from activated microglia [18]. Hence, we hypothesized that EDA inhibits mitochondrial depolarization and reduces ROS production in Aβ-treated microglia.…”
Section: Eda Reduces Mitochondrial Depolarization and Ros Levels In Amentioning
confidence: 99%